The many roles of the eukaryotic elongation factor 1 complex - Sasikumar, Arjun N; Perez, Winder B; Kinzy, Terri Goss (Wiley interdisciplinary reviews. RNA, 2012)
The vast majority of proteins are believed to have one specific function. Throughout the course of evolution, however, some proteins have acquired additional functions to meet the demands of a complex cellular milieu. In some cases, changes in RNA or protein processing allow the cell to make the most of what is already encoded in the genome to produce slightly different forms. The eukaryotic elongation factor 1 (eEF1) complex subunits, however, have acquired such moonlighting functions without alternative forms. In this article, we discuss the canonical functions of the components of the eEF1 complex in translation elongation as well as the secondary interactions they have with other cellular factors outside of the translational apparatus. The eEF1 complex itself changes in composition as the complexity of eukaryotic organisms increases. Members of the complex are also subject to phosphorylation, a potential modulator of both canonical and non-canonical functions. Although alternative functions of the eEF1A subunit have been widely reported, recent studies are shedding light on additional functions of the eEF1B subunits. A thorough understanding of these alternate functions of eEF1 is essential for appreciating their biological relevance.